Spatial Analysis of Commercial Services in Poland - Gibas, Piotr; Twardzik, Małgorzata (IOP conference series. Materials Science and Engineering, 2020)
Trade is the subject of interest in many areas of science, such as geography, economics, marketing, sociology or urban planning. In many countries in Europe and the USA, studies of trade usually focus on the location of commercial outlets in urban space, accessibility (time, cost) of the trade for customer, selection of assortment offers and innovations in trade. A recent decade of spatial studies on trade in Poland concerns mainly new large-selling area formats and the importance of trade in the development of the suburbanization process and appropriation of public space by new trade formats. The aim of the article is to identify the mains rightness of the locations of commercial and service buildings in Polish towns and rural areas and to determine the percentage of the population living in areas with difficult access to the trade. Conducted statistical and spatial analysis with the use of information obtained from Database of Topographic Objects is a method of diagnosis of accessibility that has not been applied before for its entire area of Poland and constitutes the introduction for further in-depth studies in this sphere. Trade is one of the most important sectors of the national economy in Poland and an essential market component both on regional and local scale. It is also a vital element of the expanded distribution system and thus it affects the quality of people's lives while satisfying their consumer needs in the sphere of buying goods in convenient time, place and conditions guaranteeing a high quality of provided services. The city remains a natural environment of commercial activity as the development processes constantly proceed there, new consumer needs occur and new trade forms (e.g. large selling area super and hypermarkets as well as shopping malls) emerge there. Commercial activity depends on other city functions, including communication as well as social and economic functions, thus it directly affects the shaping of the majority of functional elements in the city and conditions of its competitiveness as the center of the settlement system. Distribution of commercial outlets in a given area determines the availability of goods and creates conditions for efficient provision of services for residents. The paper is a statistical and spatial analysis of commercial services in Poland.